COMPARISON OF SEMI-CLASSICAL AND QUANTUM-MECHANICAL CROSS-SECTIONS AND RATE CONSTANTS FOR CO2(0110)+M-]CO2(0000)+M(M=HE,NE) - Billing, G; Clary, D (1982)
Cross sections and rate constants are calculated for the deactivation of the bending vibrational mode of the CO2 molecule colliding with He and Ne. Results obtained using semiclassical, semiclassical sudden and quantum vibration infinite-order-sudden methods are compared. © 1982.